Kebijakan Bahasa Lokal dalam Produksi Majalah Manglé di Bogor - Rodhiya, Faz'alny Robby; Hidayah, Adinda Rohman; Aulia, Nindy Rezq; Zenfin, Yulia Fitriani; Widyastuti, Temmy (Faculty of Da'wa and Communications Sciences, 2025)
This research aims to find out the language policy used by Manglé magazine in producing regional language magazines and its relation to the language policy issued by the government. This research is a qualitative research using descriptive analysis method and interview technique. The language policy is used in the production of Manglé magazine is to use journalistic language and not to prioritize certain dialects. Manglé remains means of preserving local languages through printed entertainment media. This research covers all the strategies of the magazine to survive in the current era of the cutting age of media technology. Going through rough challenges, Manglé consistently produces the Sundanese local wisdom by reaching its 3000th edition. Keywords: Language policy, Manglé Magazine, Regional Languages